Hybrid Digital Twin Model for Greenhouse and Underground Environments - Soto-Gomez, J; Kern-Falcon, W (Institute of Electrical and Electronics Engineers Inc., 2024)
This research delves into the application of Digital Twins (DTs) in the realm of smart agriculture, with a particular focus on greenhouse and underground environments. By integrating computer simulations with empirical testing, we validate our hypotheses. A novel approach has been introduced that uses Visible Light Communication (VLC) for data exchange within greenhouses, along with a distinct system tailored for subterranean applications. This investigation explores how various factors influence communication effectiveness. Comprehensive testing of these systems has been conducted to evaluate their performance under a range of conditions and with varying orientations of light sources. Specifically, for our greenhouse configuration, we discovered that adjusting the system in a specific manner can substantially enhance signal quality, by nearly 10 dB at a distance of four meters, in underground scenarios. Furthermore, we have conducted evaluations using the most current WiFi and mobile networks, as well as Free Space Optics (FSO) networks, to ensure that our digital twin model is robust and capable of accurately transmitting data to a control room. © 2023 IEEE.